Effects of sacubitril/valsartan in ESRD patients undergoing hemodialysis with HFpEF - Guo, Yanhong; Ren, Mingjing; Wang, Tingting; Wang, Yulin; Pu, Tian; Li, Xiaodan; Yu, Lu; Wang, Liuwei; Liu, Peipei; Tang, Lin (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Heart failure with preserved ejection fraction (HFpEF), which is a common complication in maintenance hemodialysis (MHD) patients, results in substantial mortality and morbidity. However, there are still no effective therapeutic drugs available for HFpEF currently. Sacubitril/valsartan had been showed to significantly improve clinical outcomes and reverse myocardial remodeling among patients with heart failure with reduced ejection fraction. The effect of sacubitril/valsartan in MHD patients with HFpEF remains unclear. Our study was designed to assess the efficacy and safety of sacubitril/valsartan in MHD patients HFpEF. Methods: A total of 247 MHD patients with HFpEF treated with sacubitril/valsartan were included in this study. Patients were followed up regularly after medication treatment. The alterations in clinical, biochemical, and echocardiographic parameters before and after taking sacubitril/valsartan were collected. In addition, safety of the sacubitril/valsartan treatment was also assessed. Results: Among those 247 MHD patients, compared with baseline levels, systolic blood pressure (BP) (149.7±23.6 vs 137.2±21.0 mmHg, P<0.001), diastolic BP ( 90.2±16.1 vs 84.5±14.1 mmHg, P<0.001), heart rate (83.5±12.5 vs 80.0±8.7 bpm, P<0.001), N- terminal B- type natriuretic peptide precursor [29125.0 (11474.5, 68532.0) vs 12561.3 (4035.0, 37575.0) pg/ml, P<0.001], and cardiac troponin I [0.044 (0.025，0.078) vs 0.0370 (0.020, 0.064) µg/L, P=0.009] were markedly decreased after treatment with sacubitril/valsartan. New York Heart Association functional class showed a notable trend of improvement after 3–12 months of follow-up. Echocardiographic parameters including left ventricular posterior wall thickness (11.8±2.0 vs 10.8±1.9 mm, P<0.001), intraventricular septal thickness in diastole (11.8±2.0 vs 11.2±2.0 mm, P<0.001), left ventricular end-diastolic diameter (53.8±6.9 vs 51.2±7.1 mm, P<0.001), left atrial diameters (40.5±6.2 vs 37.2±7.2 mm, P<0.001), left ventricular end-diastolic volume [143.0 (111.5, 174.0) vs 130.0 (105.0, 163.0) mL, P<0.001], left ventricular end-systolic volume, and pulmonary arterial systolic pressure were significantly reduced after initiating the treatment of sacubitril/valsartan. The parameters of left ventricular diastolic function including E/A ratio, maximal tricuspid regurgitation velocity, septal e’ wave velocity, lateral e′ wave velocity , and left artial volume index were significantly improved by the sacubitril/valsartan. Conclusion: Our study suggested that sacubitril/valsartan treatment in MHD patients with HFpEF was effective and safe.